2008
DOI: 10.1128/cvi.00184-08
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD40 Ligand Response in Monocytes from Sepsis Patients

Abstract: It has been suggested that a defective adaptive immune response contributes to septic immunosuppression. Here, the response of monocytes to CD40 ligand (CD40L) for patients with sepsis due to infection with gram-negative organisms has been analyzed. Compared to cells from controls, monocytes from septic patients showed significantly reduced production of tumor necrosis factor alpha, interleukin-1␤ (IL-1␤), and IL-12 and were unable to acquire high levels of CD80 and CD86 molecules. These alterations were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…The main receptor of CD40L is CD40, and it is interesting to note that a recent study demonstrated increased expression of both CD40L and CD40 on monocytes in sepsis [8]. Somewhat in contrast to that observation, Sinistro et al [9] reported that CD40-mediated stimulation of septic monocytes is attenuated in terms of cytokine production and expression of co-stimulatory molecules. CD40L (CD154) is a member of the tumour necrosis factor (TNF) family and is expressed as a transmembrane protein in activated platelets [10].…”
Section: Introductionmentioning
confidence: 51%
“…The main receptor of CD40L is CD40, and it is interesting to note that a recent study demonstrated increased expression of both CD40L and CD40 on monocytes in sepsis [8]. Somewhat in contrast to that observation, Sinistro et al [9] reported that CD40-mediated stimulation of septic monocytes is attenuated in terms of cytokine production and expression of co-stimulatory molecules. CD40L (CD154) is a member of the tumour necrosis factor (TNF) family and is expressed as a transmembrane protein in activated platelets [10].…”
Section: Introductionmentioning
confidence: 51%
“…And secondly, sepsis induces a number of stimuli that trigger lymphocyte apoptosis (18). Further, we postulate that the persistent lymphopenia seen in non-survivors is most likely due to ongoing sepsis-induced lymphocyte apoptosis secondary to continued release of pro-apoptotic stimuli during the immunosuppressive phase of sepsis (12,3234). These findings are especially striking because the optimal host response to infection should be to increase lymphocyte proliferation and thereby augment the number of lymphocyte effector cells.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known, however, that monocytes show severe functional deficits which contribute to the immunosuppressive state in septic patients (3436). Laboratory procedures designed to identify monocytic defects (such as measurement of monocyte human lymphocyte antigen (HLA)-DR expression or ex vivo lipopolysaccharide (LPS)-induced tumor necrosis factor-alpha (TNF-_) levels) have successfully been shown to predict survival in septic patients (3639).…”
Section: Discussionmentioning
confidence: 99%
“…CD40L is expressed on activated CD4 lymphocytes and binds CD40 of monocytes during antigen presentation. Circulatory concentrations of sCD40L are considered a reflection of the expression of CD40L (17). As a consequence, since the levels of sCD40L did not change upon treatment with clarithromycin, whereas the expression of CD86 on monocytes was increased in parallel, it may be postulated that therapy with clarithromycin was accompanied by more efficient antigen presentation.…”
Section: Figmentioning
confidence: 99%